Ni Hao from the New Editor of the IJANR - Ur Rehman Nasar, Mujeeb (International Journal of Antibiotic Research, 2018)
An editorial from the new editor outlines the journal's mission and priorities in antibiotic research. It emphasizes methodological rigor, data transparency, and applied relevance to stewardship and resistance mitigation, inviting contributions across discovery, surveillance, and policy.
Keywords: Antibiotic Research; Stewardship; Resistance Mitigation; Data Transparency; Surveillance